An energy flow approach for progressive collapse assessment. (1st July 2019) - Wilkes, J.; Krauthammer, T.
Highlights: A method assessing a structure's progressive collapse (PC) vulnerability is proposed. The proposed energy flow approach (EFA) illustrates an energy – failure correlation. This EFA predicts failure using Energy Flow vs Energy Flow Rate (E-R) failure thresholds. This EFA to predicts PC of a damaged mid-rise steel building with repeatable accuracy. The DOD's Alternate Path (AP) method approaches for PC is shown to be ineffective. Abstract: This paper explains the correlation of energy flow and the rate energy flow to the susceptibility of progressive collapse (PC) for typical mid-rise steel framed buildings. Energy-time histories of structural members were analysed to determine the energy flow behaviour throughout the structural system. All structural elements, including all connections, were represented numerically to (more accurately) determine the building's susceptibility to PC, including the sequence of failing members. Assessing PC susceptibility with the incorporation of the rate of energy flow for a structure that accounts for the effects of connection resistance functions constitutes a novel approach. Advanced nonlinear transient dynamic finite element simulations were used to reveal the energy flow and its flow rate, and the de facto relationship with building response and failure. In addition, the efficacy of the current DOD approaches for PC assessment are examined in a comparative study with the proposed energy flow approach.